2013
DOI: 10.7567/jjap.52.04cb11
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Local Bending Stress Effect on Complementary Metal–Oxide–Semiconductor Characteristics in Thinned Si Chip for Chip-to-Wafer Three-Dimensional Integration

Abstract: A three-dimensional LSI (3D-LSI) that vertically stacks Si chips with a number of through-silicon vias (TSVs) and metal microbumps has attracted much attention recently. However, there are some issues to be resolved in the fabrication of 3D-LSI. In this study, we investigated impacts of local bending stress on the performance of a complementary metal–oxide–semiconductor (CMOS) circuit fabricated in a thinned Si chip. First, we proposed a novel method and a test structure to easily induce the local bending stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Some of ultra-thin CMOS inverters reported in the literature are summarized in Table VI. 186,[188][189][190][191] Only few of them have investigated the effect of bending stress on the performance. The performance of the thinned Si CMOS inverter circuit by Kino et al 191 degrades under bending stress, as shown in Fig.…”
Section: Invertersmentioning
confidence: 99%
“…Some of ultra-thin CMOS inverters reported in the literature are summarized in Table VI. 186,[188][189][190][191] Only few of them have investigated the effect of bending stress on the performance. The performance of the thinned Si CMOS inverter circuit by Kino et al 191 degrades under bending stress, as shown in Fig.…”
Section: Invertersmentioning
confidence: 99%
“…On the other hand, we have to be careful for Cu contamination from the Cu-TSV and the backside surface in the via-middle process since the process temperature is higher than that of back-via process [23,24,25]. Mechanical stress induced by Cu-TSVs and metal microbumps, and crystal defects and crystal structure changes produced by thinning the Si substrate are also big concerns in 3D LSIs [26,27]. Both tensile and compressive stresses are induced by Cu-TSVs and metal microbumps.…”
Section: (C)mentioning
confidence: 99%
“…As shown in Fig.1, this CTE mismatch induces local bending stress in thinned Si chips/substrates. In addition, this local bending stress would affect MOSFET performance in thinned Si chips [4]. One of the causes of this issue is temperature change due to cooling after heat curing.…”
Section: Introductionmentioning
confidence: 99%